2001
DOI: 10.1074/jbc.m011681200
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Telangiectasia Mutated (ATM) Kinase and ATM and Rad3 Related Kinase Mediate Phosphorylation of Brca1 at Distinct and Overlapping Sites

Abstract: Recent studies have provided evidence that breast cancer susceptibility gene products (Brca1 and Brca2) suppress cancer, at least in part, by participating in DNA damage signaling and DNA repair. Brca1 is hyperphosphorylated in response to DNA damage and co-localizes with Rad51, a protein involved in homologousrecombination, and Nbs1⅐Mre11⅐Rad50, a complex required for both homologous-recombination and nonhomologous end joining repair of damaged DNA. Here, we report that there is a qualitative difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 21 publications
(19 reference statements)
5
150
0
2
Order By: Relevance
“…Recently it was shown that downregulation of the Chk1 kinase has a major effect on fragile site stability , hence the effect of ATM on the level of Chk1 phosphorylation is probably part of the mechanism by which ATM regulates fragile site expression. It is worth noting that in addition to Chk1, other shared targets of ATR and ATM (BRCA1, SMC1 and FANCD2) (Gatei et al, 2001;Kim et al, 2002;Ho et al, 2006) were also shown to regulate fragile site stability (reviewed by Arlt et al, 2006). Further studies are required to investigate the regulation of these proteins by ATR and ATM, under conditions that induce fragile site expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that downregulation of the Chk1 kinase has a major effect on fragile site stability , hence the effect of ATM on the level of Chk1 phosphorylation is probably part of the mechanism by which ATM regulates fragile site expression. It is worth noting that in addition to Chk1, other shared targets of ATR and ATM (BRCA1, SMC1 and FANCD2) (Gatei et al, 2001;Kim et al, 2002;Ho et al, 2006) were also shown to regulate fragile site stability (reviewed by Arlt et al, 2006). Further studies are required to investigate the regulation of these proteins by ATR and ATM, under conditions that induce fragile site expression.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 is also an ATM substrate and is phosphorylated on Ser1387, Ser1423 and Ser1524 after DNA damage (Cortez et al, 1999;Gatei et al, 2001). Phosphorylation of BRCA1 on these sites is closely linked to S-phase and G2/M checkpoints (Xu et al, 2001.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
“…Over the last few years, BRCA1 has been identified as a target for several upstream nuclear PI-like kinases: ATM and ATR, (Cortez et al, 1999;Chen, 2000;Tibbetts et al, 2000;Gatei et al, 2001). After DNA damage, BRCA1 is phosphorylated in vitro and in vivo on S1423 and S1524 by both ATM and ATR (see Fig.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…2). However, a study utilizing a series of BRCA1 phospho-specific antibodies and cells deficient for ATM or ATR revealed that ATM mediates these phosphorylations in response to ionizing radiation (IR), while ATR mediates the phosphorylations in response to ultraviolet-C (UV) irradiation (Gatei et al, 2001). In addition, S1387 was specifically phosphorylated after IR, while S1457 was phosphorylated predominantly after UV treatment.…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%